Legal Protection for Notaries in Implementing the Principle of Recognizing Service Users in the Prevention of Money Laundering and Terrorism Financing Crime - Riska Salmaningrum; Madjid , Abdul; Wisnuwardhani, Dyah Aju (International Journal of Islamic Education, Research and Multiculturalism (IJIERM), 2025)
This research discusses the normative conflict between the obligation of notaries to maintain the confidentiality of client information as stipulated in the Notary Position Law (UUJN) with the obligation to report suspicious transactions to PPATK as stipulated in Permenkumham No. 9 of 2017 concerning the Implementation of the Principle of Recognizing Service Users (PMPJ). This study aims to identify the appropriate form of legal protection for notaries in carrying out these obligations, and analyze whether there is a conflict of norms between Permenkumham No. 9 of 2017 and UUJN. Using a normative juridical approach with statutory, conceptual, and case approach methods, this research finds that notaries are in a legally dilemmatic position. On the one hand, the Permenkumham requires the reporting of suspicious financial transactions as a form of participation in the prevention of money laundering and terrorism financing. On the other hand, UUJN explicitly requires notaries to maintain the confidentiality of deeds and client information, even threatening criminal and administrative sanctions if the obligation is violated. Provisions in Permenkumham that do not have an explicit basis in the law cause legal uncertainty. Therefore, harmonization between the PPTPPU Law, Permenkumham No. 9/2017, and UUJN is needed so that the reporting obligation by notaries does not violate the principle of official secrecy. This research also recommends strengthening preventive and repressive legal protection, as well as training and technical guidance for notaries so that they can carry out reporting obligations professionally without compromising their professional integrity.